Answer:
![\boxed{\sf (f - g)(x) = 2x - 3}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%5Csf%20%28f%20-%20g%29%28x%29%20%3D%202x%20-%203%7D%20)
Given:
f(x) = 3x - 1
g(x) = x + 2
To Find:
(f - g)(x)
Step-by-step explanation:
![\sf (f -g)(x) = f(x) - g(x) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =(3x - 1) - (x + 2) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =3x - 1 - x - 2 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =3x - x - 1 - 2 \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =(3x - x) - (1 + 2) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =2x - (1 + 2) \\ \\ \sf \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: =2x - 3](https://tex.z-dn.net/?f=%5Csf%20%28f%20-g%29%28x%29%20%3D%20f%28x%29%20-%20g%28x%29%20%5C%5C%20%5C%5C%20%20%20%5Csf%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%3D%283x%20-%201%29%20-%20%28x%20%2B%202%29%20%5C%5C%20%20%5C%5C%20%5Csf%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%3D3x%20-%201%20-%20x%20-%202%20%5C%5C%20%20%5C%5C%20%5Csf%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%3D3x%20-%20x%20-%201%20-%202%20%5C%5C%20%20%5C%5C%20%5Csf%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%3D%283x%20-%20x%29%20-%20%281%20%2B%202%29%20%5C%5C%20%20%5C%5C%20%5Csf%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%3D2x%20-%20%281%20%2B%202%29%20%5C%5C%20%20%5C%5C%20%5Csf%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%3D2x%20-%203)
Since s and t are complimentary, that means ∠s + ∠t = 90
From the picture, we also know that ∠t + ∠LGM = 90
Set them equal to each other:
∠s + ∠t = ∠t + ∠LGM, solve:
∠s = ∠LGM
Now using the fact that tangent = opposite/adjacent:
tan (∠s) = ![\frac{y}{h}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7Bh%7D)
tan (∠s) = ![\frac{h}{x}](https://tex.z-dn.net/?f=%5Cfrac%7Bh%7D%7Bx%7D)
Set them equal to each other to get:
= ![\frac{h}{x}](https://tex.z-dn.net/?f=%5Cfrac%7Bh%7D%7Bx%7D)
Solve:
![h^{2}= xy\\h = \sqrt{xy}](https://tex.z-dn.net/?f=h%5E%7B2%7D%3D%20xy%5C%5Ch%20%3D%20%5Csqrt%7Bxy%7D)
Part B:
Using tan (∠s) = ![\frac{y}{h}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7Bh%7D)
We get:
meters
Hope that helps!
Answer:
BAngle AOB is half as big as angle COB.
Answer:
(A,C)
Step-by-step explanation:
i think